Tofacitinib as salvage therapy for 55 patients hospitalised with refractory severe ulcerative colitis: A GETAID cohort. Issue 3 (20th June 2021) - Uzzan, Mathieu; Bresteau, Clément; Laharie, David; Stefanescu, Carmen; Bellanger, Christophe; Carbonnel, Franck; Serrero, Mélanie; Viennot, Stéphanie; Nachury, Maria; Amiot, Aurélien; Altwegg, Romain; Picon, Laurence; et al.
Summary: Background: Up to 25% of patients with ulcerative colitis (UC) will require hospitalization for severe flare. In patients hospitalised for severe flare, who previously experienced multiple drug failures, including steroids and anti‐TNF agents, new quick‐acting medical options are needed. Tofacitinib is effective in refractory UC and has a rapid onset of action. Aim: To evaluate effectiveness and safety of tofacitinib as rescue therapy in patients hospitalised for UC flare. Methods: We conducted an observational and multicentre study with both retrospective and prospective collections in 14 GETAID centres. The primary objective was to assess the survival without colectomy following tofacitinib initiation in patients hospitalised for a UC flare. We determined rates of clinical response, clinical remission, and steroid‐free clinical remission at week 6 and week 14 and safety. Results: Fifty‐five patients were included (49 with prior infliximab failure and 19 previously exposed to ciclosporin). With a median follow‐up of 6.5 months (interquartile range [IQR] [3‐12.3]), rate of colectomy‐free survival was estimated at 78.9% (95 CI [68.5‐90.9]) and 73.6% (95 CI [61.9‐87.3]) at 3 and 6 months, respectively. Rates of clinical response, clinical remission and steroid‐free clinical remission were 60%, 45.5% and 37.5% at week 6 and 41.8%, 34.5% and 32.7% at week 14. Regarding safety, no death was observed, three patients withdrew tofacitinib due to adverse events. Two herpes zoster infections occurred in patients aged over 60 years old. No venous thrombotic or major adverse cardiovascular events occurred. Conclusion: Tofacitinib appears as a promising option in patients hospitalised with a UC flare but needs further validation in controlled trials. Abstract : In a cohort of biologic‐experienced patients hospitalised for a severe flare of ulcerative colitis, tofacitinib allowed to avoid colectomy in a substantial proportion of patient, with a colectomy‐free survival of 78.9% (95CI [68.5‐90.9]) at 3 months.